Islamization and the representation of Islam in Yoruabland of Southwestern Nigeria: an exploratory study with special reference to Jalabi phenomenon = Pengislaman dan perwakilan Islam di Yoruabland di baratdaya Nigeria: satu kajian eksploratori dengan rujukan khas terhadap fenomena jalabi - Musa, Afiz Oladimeji; Ibrahim, Hassan Ahmed (International Islamic University Malaysia, 2015)
Jalabi is an extant historical phenomenon with strong socio-religious impacts in Yorubaland, south-western part of Nigeria. It was a strategy devised by the Yoruba ‘UlamÉ’ as one of the many effective ways to represent Islam among the indigenous people for the purpose of spreading and consolidating Islam. This strategy is reflected in certain spiritual services rendered to the people, which include, but not limited to, spiritual consultation and healing, such as petitionary Du‘É (prayer), divination through sand-cutting, rosary selection, charm-making, etc. This paper represents an effort to study and investigate both positive and adverse effects of this long-standing phenomenon on the socio-religious life of the Yoruba people of Nigeria.